NEED-ANALYSIS BASED ON DESIGN PROPER ENGLISH COURSE SYLLABUS - Rahmawan, Andi Dian (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
This research attempts to give perspective to the teachers and lecturers of English regarding a proper syllabus which mainly based on students’ problems on designing good quality of the abstracts of their research. 14 students’ product of abstracts of non-English department in the University of PGRI Yogyakarta would be employed as the main sources of data. The technique of doing this study is by observing on the students’ error production based on the diction and the grammatical aspects. This is a Research and Development which the result is a need-analysis-based syllabus. The syllabus mirrors that most of students have difficulties on finding the proper dictions of certain words, such as cardinal and ordinal numbers. From the perspective of grammar, they found that it is an obstacle to apply certain tense and aspect system of English. Based on these, the researcher expects that teacher and lecturer of English are able to design the more suitable and ready-to-use skills that gained during the classroom activities so that students are able to design the more acceptable abstract of their research to increase the readability and the acceptability of academic writing.